Pelatihan Desain Grafis dengan Aplikasi Canva untuk Siswa SMP 4 Muaro Jambi - Lestrari, Agus; Pratama, Muhammad Arya; Pratama, Maynanda; Prandika, Noval Dwi; Hanapi, Muhammad Harli (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article aims to hold a graphic design training using the Canva application for students of SMP Negeri 4 Muaro Jambi. With the rapid development of information and communication technology, education now benefits greatly from faster access to information and more flexible learning methods, such as online learning and blended learning. The method used in this training is service learning, which combines academic learning with community empowerment efforts. The training took place with two main agendas, namely the introduction of Canva features and a poster making competition. The results of the training show that students and teachers are interested in using Canva as a tool in the learning process, and can create design works that can be published on social media or used for other purposes. This study concludes that the use of the Canva application provides long-term benefits in improving students' creativity and digital skills, as well as making it easier for educators to deliver learning materials